Nursing Supervision Model toward Patient Safety Goals On The Ward - Nursalam . (Journal of Global Pharma Technology, 2016)
Clinical supervision of interactive reflective model is a guideline for the implementation of patient safety goals at the hospital. This supervision supports the one who is supervised to improve self-awareness and professional development in the implementation of patient safety goals. The purpose of this research was to find out the influence of reflective interactive supervision model toward the implementation of patient safety goals. The method used is quasi-experimental with pretest-posttest with control group design. There were 24 subjects in interventions and 24 subjects in control group. Data were taken using a proportional stratified random sample. The data were analyzed by using chi-square, independent sample t-test, paired sample t-test, Pearson correlation, and general linear model repeated measure was used for multivariate analysis. The result shows that there are significant differences after the implementation of interactive reflective supervision (p < 0.000). The average achievement score of the implementation of patient safety goals between groups shows a significant difference. In the intervention group, the achievement score began to show an improvement starting from the second measurement and the maximum score was seen in the fifth measurement. Clinical supervision interactive reflective model is potentially required by the head nurse as a guideline for supervising the implementation of the patient's safety goals in the hospital.Keywords: Supervision, Interactive reflective, Patient safety goal, Hospital.